2019
DOI: 10.1002/pbc.27961
|View full text |Cite
|
Sign up to set email alerts
|

Current practices in menstrual management in adolescents with cancer: A national survey of pediatric oncology providers

Abstract: Background Adolescents and young adult (AYA) women with cancer are at risk of heavy menstrual bleeding (HMB) due to thrombocytopenia, coagulopathy, and/or disruption of the hypothalamic‐pituitary‐gonadal axis. Currently, little is known about current practices to help prevent and treat HMB in AYA women with cancer. Methods We surveyed providers from 100 pediatric oncology centers. Face and content validity were assessed prior to distribution. Descriptive statistics, Chi‐squared and Fisher exact tests were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…38,39 Pubertal females should understand that the benefits of GnRH agonists in the adolescent young adult population are unknown, and the use of GnRH agonists should not be thought of as fertility preservation and used in place of established forms of fertility preservation. There are data for the use of these agents for menstrual suppression, 40 which may be considered in a variety of patients but are of particular interest for patients expected to have prolonged thrombocytopenia or with a history of heavy menses. 40,41 Due to the limitations of available fertility preservation options in the leukemia/lymphoma population, many young women may not be able to undergo upfront fertility preservation.…”
Section: Gonadotoxic Therapymentioning
confidence: 99%
“…38,39 Pubertal females should understand that the benefits of GnRH agonists in the adolescent young adult population are unknown, and the use of GnRH agonists should not be thought of as fertility preservation and used in place of established forms of fertility preservation. There are data for the use of these agents for menstrual suppression, 40 which may be considered in a variety of patients but are of particular interest for patients expected to have prolonged thrombocytopenia or with a history of heavy menses. 40,41 Due to the limitations of available fertility preservation options in the leukemia/lymphoma population, many young women may not be able to undergo upfront fertility preservation.…”
Section: Gonadotoxic Therapymentioning
confidence: 99%
“…It is noteworthy that in adolescents and young women with malignancies GnRHa are widely used as an alternative to estroprogestinic combinations for menstrual suppression (36)(37)(38)(39)(40)(41), in order to reduce the risk of heavy menstrual bleeding associated with hematologic malignancies or myelosuppression induced by chemotherapy. In this setting, despite significant side-effects simulating the physiology of menopause and the risk of loss of bone mineral density with prolonged use (usually > 6 months) (42), GnRHa are well tolerated and effective option for menses suppression (43,44) and are generally preferred to oral contraceptives for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the efficacy of oral contraceptives can be reduced by an erratic absorption due to mucositis, diarrhea, and emesis. Moreover, the use of estrogen-based oral contraceptives for menstrual suppression is associated with an increased risk of venous thromboembolism (41,45). However, one of the most important reason for choosing GnRHa is represented by their possible gonadal protective effect (41).…”
Section: Introductionmentioning
confidence: 99%
“…32 Prior research has found that people with cancer wish they had been better prepared for potential reproductive issues by their cancer providers. 5 Treatment-induced amenorrhea can be a sign of adversely affected fertility 33 and premature menopause, which warrants consideration of HRT, calcium, vitamin D, bisphosphonates, and exercise to manage menopausal symptoms and negative cardiovascular sequelae. 4,34,35 In some patients, HRT may be contraindicated due to the underlying malignancy (eg, hormonesensitive breast cancer); however, evidence supports an individual risk-benefit assessment.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Chemotherapy predisposes people who menstruate to heavy menstrual bleeding due to thrombocytopenia, coagulopathy, or disruption of the hypothalamic-pituitarygonadal axis. [5][6][7] Other disturbances, such as anovulatory bleeding and amenorrhea, are also prevalent. Menorrhagia, typically defined by .80 mL of blood loss per cycle or bleeding for .7 days, increases infection risk in immunosuppressed patients with associated neutropenia, 6 and potentiates iron deficiency, anemia, and thrombocytopenia, necessitating transfusion.…”
Section: Introductionmentioning
confidence: 99%